Environmental quality assessment of sandy beaches in Ha Long - Cat Ba area (Vietnam) - Thu Trang, Cao Thi; Tran Dinh, Lan; Do Thi, Thu Huong; Tran Manh, Ha; Nguyen Thi, Thu Ha; Pham Thi, Kha; Nguyen Van, Bach; Le Van, Nam; Dinh Hai, Ngoc (Vietnam Journal of Marine Science and Technology, 2022)
The environmental quality of 6 famous sand beaches of the Ha Long - Cat Ba area was surveyed in July 2018 (the rainy season) and March 2019 (the dry season). The results showed that the pore water layer below the sand surface contained some pollutants exceeding the critical value of QCVN 10:2015/BTNMT for coastal water and ASEAN-criteria, including TSS, ammonium and nitrate. In the rainy season, the pore water quality was lower than that in the dry season, indicating that the tourism influenced the sandy beach water quality. Among the studied beaches, Ha Long and Bai Dai (Van Don) showed pore water pollution; the rest beaches were low to moderate pollution. Pore water in sandy beaches was charecterized by low dissolved oxygen saturation and high mineralization compared to sea water, thus confirming the role of sandy beaches in providing mineral nutrients to the sea. Analysis of the sediment grain size at the sandy beaches showed that the beach quality was medium to good. Forty-seven benthic fauna species were found on sandy beaches of the Ha Long - Cat Ba area, of which the dominant species were mollusks, followed by crustaceans, polychaetes, and echinoderms. The biodiversity of sandy beaches in study area was at an average level.